The First Terrestrial Electron Beam Observed by the Atmosphere‐Space Interactions Monitor. Issue 12 (10th December 2019) - Sarria, D.; Kochkin, P.; Østgaard, N.; Lehtinen, N.; Mezentsev, A.; Marisaldi, M.; Carlson, B. E.; Maiorana, C.; Albrechtsen, K.; Neubert, T.; Reglero, V.; Ullaland, K.; et al.
Abstract: We report the first Terrestrial Electron Beam detected by the Atmosphere‐Space Interactions Monitor. It happened on 16 September 2018. The Atmosphere‐Space Interactions Monitor Modular X and Gamma ray Sensor recorded a 2 ms long event, with a softer spectrum than typically recorded for Terrestrial Gamma ray Flashes (TGFs). The lightning discharge associated to this event was found in the World Wide Lightning Location Network data, close to the northern footpoint of the magnetic field line that intercepts the International Space Station location. Imaging from a GOES‐R geostationary satellite shows that the source TGF was produced close to an overshooting top of a thunderstorm. Monte‐Carlo simulations were performed to reproduce the observed light curve and energy spectrum. The event can be explained by the secondary electrons and positrons produced by the TGF (i.e., the Terrestrial Electron Beam), even if about 3.5% to 10% of the detected counts may be due to direct TGF photons. A source TGF with a Gaussian angular distribution with standard deviation between 20.6° and 29.8° was found to reproduce the measurement. Assuming an isotropic angular distribution within a cone, compatible half angles are between 30.6° and 41.9°, in agreement with previous studies. The number of required photons for the source TGF could be estimated for various assumption of the source (altitude of production and angular distribution) and is estimated between 10 17.2 and 10 18.9 photons, that is, compatible with the current consensus. Plain Language Summary: Terrestrial Gamma Ray Flashes (TGFs) are the highest energy natural particle acceleration phenomena occurring on Earth. They are burst of energetic photons associated with thunderstorms and have a poorly understood production mechanism. When interacting with the atmosphere, TGFs produce secondary electrons and positrons of high energy. A fraction of them can reach space and forms a beam under the effect of Earth's magnetic field, so called Terrestrial Electron Beam (TEB). They can be detected over geographical location with no lightning activity. In the past, most of the TEBs have been detected by the Fermi space telescope and the Compton Gamma ray Observatory. In this article, we report the first detection of a TEB by the Atmosphere‐Space Interactions Monitor, docked on the International Space Station since April 2018. During this event, no lightning activity was detected below the instrument. The TEB's source lightning was actually found to be located 650 km away from detector, very close to an overshooting top of a thundercloud. The comparison of the observation with simulated data made it possible to constrain the geometry of the parent TGF. Our results point toward a relatively wide angular distribution and an intensity of 10 17.2 to 10 18.9 photons, in agreement with previous studies. Key Points: Flying over an area with no nearby lightning activity, the ASIM‐MXGS instrument detected a 4 ms long event with a soft spectrum Observations coupled with simulations suggest that more than 90% of the counts come from a TEB and the rest from the associated TGF A source TGF with a broad angular distribution and 10 17 to 10 19 photons can explain the observation